Potensi Baitul Maal Wat Tamwil (BMT) dalam Meningkatkan Pertumbuhan Ekonomi di Indonesia - Sahil , Irdlon (LPPPM STAI Darul Hikmah Bangkalan, 2019)
The study was intended to explain the potential Baitul Maal wat Tamwil for bringing economic growth to Indonesia. This method of research is done by reading reference books, journals and other media related to BMT. The concept of Baitul Maal wat Tamwil is to develop productive businesses and invest in developing the quality of macro and small economic activities, in part, it encourages savings and financing its economic activities. BMT is made up of two main functions: Baitul Tamwil (property development home), and Baitul Maal (treasure). This study shows that BMT has the potential to increase economic growth in Indonesia. It’s proven by several journals that there are among them as INFERENSI (a religious social research journal), SOSIO DIDAKTIKA: Social Science Education Journal, and HUMAN FALAH